THE EFFECT OF NUTRITION EDUCATION USING TIKTOK AND INSTAGRAM SOCIAL MEDIA ON INCREASING BALANCED NUTRITION KNOWLEDGE IN OVERNOURISHED ADOLESCENTS AT SMP NEGERI PRINGSEWU - Luci Anggraini; Desti Ambar Wati, S.Gz., M.Gz (Universitas Widya Gama Mahakam Samarinda, 2024)
Abstract Background: Nutritional Knowledge Is one of the factors that affect the nutritional status of adolescents. One effort to improve adolescent knowledge regarding balanced nutrition is to provide education using the right methods and media. The use of social media can be a promising solution for nutritional interventions, especially among adolescents, Tiktok and Instagram are media that are almost in high demand and can be used effectively for nutritional education. The purpose of this study was to determine the effect of using social media Tiktok and Instagram as educational media on increasing knowledge of balanced nutrition in overweight adolescents at SMP Negeri Pringsewu. Objectives: To determine the influence of nutritional education using social media TikTok and Instagram on increasing knowledge of balanced nutrition among over-nourished teenagers at Pringsewu State Middle School. Research Metodes: This type of research is quantitative with a true experimental method. True Experimental is a true experiment, because in this design, the researcher can control all external variables that influence the course of the experiment. This research used a Pretest-Posttest Control Group Design, two groups were given different treatments Results: The results showed that there was a difference in knowledge (p = 0.000) which increased knowledge after education was given to the Tiktok and Instagram groups, while in the lecture group there was no difference in knowledge (p = 0.333) which did not increase knowledge after education was given to the lecture group. There was a significant difference in increasing knowledge between the Tiktok, Instagram and lecture groups (p = 0.000). Conclusion: Based on the results above, it can be concluded that there is an effect of nutrition education using Tiktok and Instagram social media on increasing knowledge of balanced nutrition in overweight adolescents at SMP Negeri Pringsewu. Keywords: Teenagers; Knowledge; Tiktok; Instagram; Balanced Nutrition Abstrak Latar Belakang: Pengetahuan Gizi Merupakan salah satu faktor yang mempen garuhi status gizi remaja. Status gizi lebih disebabkan karena kurangnya pengetahuan mengenai gizi seimbang. Upaya untuk meningkatkan pengetahuan remaja terkait gizi seimbang adalah dengan memberikan edukasi menggunakan metode dan media yang tepat. Penggunaan media sosial bisa menjadi solusi yang menjanjikan untuk intervensi gizi, terutama di kalangan remaja, Tiktok dan Instagram adalah salah satu media efektif digunakan untuk edukasi gizi. Tujuan: Untuk mengetahui Pengaruh Edukasi Gizi Menggunakan Media Sosial Tiktok dan Instagram Terhadap Peningkatan Pengetahuan Gizi Seimbang Pada Remaja Gizi Lebih Di SMP Negeri Pringsewu. Metode Penelitian: Jenis penelitian ini adalah kuantitatif dengan metode true eksperiment. True Eksperimental adalah eksperimen yang betul- betul, karena dalam desain ini, peneliti dapat mengontrol semua variabel luar yang mempengaruhi jalannya eksperimen. Penelitian ini menggunakan desain Pretest-Posttest Control Group Design, dua kelompok diberikan perlakuan yang berbeda Hasil: Hasil penelitian menunjukkan terjadi peningkatan pengetahuan setelah pemberian edukasi pada kelompok Tiktok (0,000), Instagram (0,001) dan ceramah (0,000). Terdapat perbedaan yang signifikan pada peningkatan pengetahuan antara kelompok Tiktok, Instagram dan kelompok ceramah (p=0,000). Kesimpulan: dapat disimpulkan bahwa ada pengaruh edukasi gizi menggunakan media sosial Tiktok dan Instagram terhadap peningkatan pengetahuan gizi seimbang pada remaja gizi lebih di SMP Negeri Pringsewu. Kata kunci: Remaja; Pengetahuan; Tiktok; Instagram; Gizi Seimbang